The Value of Water Connections in Central American Cities: A Revealed Preference Study - Nauges, Celine; Strand, Jon; Walker, Ian (2012)
We estimate annualized values of access to home tap water in three cities in El Salvador, and marginal 'barrios' in four Guatemalan cities, using a hedonic price method for studying changes in capitalized home values from obtaining a water connection. A tap water connection is found to add from 10 per cent to 52 per cent to sales values of homes in our sample. The estimated mean values of gaining tap water access represent 1-5 per cent of real household income, differing by city and with generally higher values in El Salvador. On average this gain eliminates between 1 per cent and 3 per cent of the initial difference in real incomes between the groups of connected and unconnected households. We also find large differences in the value of a tap connection depending on the main source of non-tap water, with lowest values when the source is a private well in El Salvador.